FACTORS AFFECTING CONSUMERS PREFERENCES FOR PURCHASE PLACE OF LOCAL FOOD PRODUCTS - E. Kadanal; N. Demir (Journal of Animal and Plant Sciences, 2018)
This study aimed to investigate the factors affecting consumers preferences for purchaseplace of local food products and comparative importance of these factors. For this purpose, a face-to-face survey of consumers was conducted in Erzurum province in Turkey. In order to analyze the data obtained, a multinomial logit model was employed. As a result of the analysis, it was determined that income level and purchase frequency were statistically significant factors in determining the preference of Y (Producer or farmer/ village market) among the alternative purchase places of local 1 food products. For Y ( special shops where local products are sold, as purchase place), occupation and purchase 2 frequency were found to be significant. The significant factors for Y ( supermarkets as purchase places) were place of 3 birth, income level, purchase frequency and whether the meaning of geographic indication is known or not. In conclusion, it is possible to evaluate the purchase place as an important factor in consumers preferences for local food products. Therefore, it could be stated that, considering factors influencing place of purchase, providing producer incentives and informational activities towards this sector could prove important. products which have a traditional feature due to
Keywords: Local product; consumer; multinomial logit; purchase place; Turkey.